Current state and future prospects of Islamic banking in Morocco: An empirical investigation - Abd Aziz, Hassanuddeen; Abdelghani, Echchabi (Journal of Emerging Economies and Islamic Research, 2015)
The purpose of the study is to review the current state of Islamic banking in Morocco, and to investigate the factors that influence the adoption of Islamic banking services in the country. Accordingly, a survey was conducted covering 400 respondents from most of the Moroccan regions, and data analysis was based on linear regression. The findings revealed that the main factors that influence the decision of the Moroccan customers to adopt Islamic banking services are relative advantage, compatibility and social influence. Furthermore, the findings revealed that the progress of Islamic banking in Morocco is faced by multiple legal and regulatory challenges.